Estudo empírico dos determinantes dos gastos com investimentos das empresas brasileiras - Bordalo, Eduardo Riedlinger Mont'Alverne (2017)
This sludy aims to analyze lhe microeconomic variabJes that influence lhe decision af Brazilian companics to makc Capital Expenditure. Four hypothesis related to lhe folJowing investment thesis were tested: Neoclassical theory, Free Cash Flow theory and Agency theory. The motivatian af this study is to understand lhe investment decision process af Brazilian fimls and compare it with similar studics applicd in developed countries outside Latin America. Furtherrnore, lhe govemment influence in lhe inveslment decision process af some ofthe firms was segregated and analyzed separately. The analysis is based on 1.520 data from quarterly financiai statements of 38 finns listed on lhe Brazilian stock exchange from 2006 to 2016. The firrns were a1so separated in two differenl groups. one of them eontaining the firms that the Brazilian govemment ean innuenee lhe Capex deeision. The results show that the sample with ali firms and the sample with fimls that do not suffer from government influenee eonfinn ali investment Iheories and indieate Ihat lhe Free Cash Flow theory is predominam in lhe Brazilian business environment. The independent variables sales. free cash flow and Tobin 's Q ratio have positive efTeet on eapex. while leverage and size have a negative effeet. The results from lhe sample with finns lhal suffer from govemment influence eonfirrn only the Neoclassical theory lhat states that the variab le sales is positively correlated with lhe Capex.